EFFECT OF FINANCIAL INDICATORS AND GOOD CORPORATE GOVERNANCE STRUCTURE ON STOCK PRICE WITH FINANCIAL DISTRESS AS ANINTERVENING VARIABLE - Dewi Silvia; Meita Sekar Sari (Prosiding International conference on Information Technology and Business (ICITB), 2018)
This study aims to test the effect of Financial Iindicator and Good Corporate Governance on stock price with Financial Distress as an intervening variable in conventional banking companieslisted on the Indonesia stock exchange (IDX) in the period of 2013-2017. The populations in this study were 5 conventional banking companies listed on the Indonesia stock exchange (IDX) in the period of 2013-2017 and the sampling technique used ramdom sampling method. This study used path analysis. The study results indicated that (1) the ratio of Liquidity had a significant effect on Financial Distres. (2) the ratio of Leverage had a significant effect on Financial Distres. (3) the ratio of Profitability had a significant effect on Financial Distress. (4) Corporate Governance structure had no significant effect on Financial Distress. (5) Financial Distress had a significant effect on the stock price Keywords: Liquidity, Leverage, Profitability, Corporate Governance, Stock Price